Narrow Band Imaging: Technology Basis and Research and Development History - Kazuhiro Gono (Korean Society of Gastrointestinal Endoscopy, 2015)
The first launch of narrow band imaging (NBI) was in 2005. Since then, in most countries where gastrointestinal endoscopies are performed, NBI is the most commonly used optical digital method of performing image-enhanced endoscopy. Thanks to the outstanding efforts of many endoscopists, many clinical studies have been performed and clinical evidence has been gathered. In Japan, since 2010, NBI has been reimbursed under the Japanese national health insurance system. This is owing to the establishment of clinical evidence by physicians. However, even though endoscope systems with NBI function have been widely used outside of Japan, dissemination of knowledge on how to use NBI is insufficient. In this review paper, the technology basis of NBI and its research and development history are described. I hope this information will be helpful for updating physicians' knowledge of NBI.